HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP PASIEN HIPERTENSI TENTANG PENGENDALIAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS SARITANI KABUPATEN BOALEMO - Ari Yudistira Perdana Tangahu; Juliati Koesrini (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2026)
Background: Hypertension is considered a silent disease because people are unaware they have it until they have their blood pressure checked. Hypertension is the leading cause of stroke, both in systolic and diastolic blood pressure (Rudianto, 2013). According to World Health Organization (WHO) data, approximately 972 million Indonesians aged 18 and over worldwide had hypertension in 2014. Based on the 2024 Boalemo Regency Health Profile, the Saritani Community Health Center had 559 hypertension sufferers. Hypertension can be prevented and controlled by promoting a healthy lifestyle. However, a lack of adequate public knowledge about hypertension and its prevention tends to increase the incidence of hypertension. The high number of hypertension cases at the Saritani Community Health Center in BoalemoRegency may be due to several factors. Some may be aware of their hypertension but have not taken any control measures, or others may be unaware of their hypertension. This is the reason why the researcher took the title of the relationship between the level of knowledge and attitudes of hypertension patients regarding hypertension control in the Saritani Community Health Center Work Area, Boalemo Regency.